PENERAPAN CRM (CUSTOMER RELATIONSHIP MANAGEMENT) PADA MITRA KELOMPOK TANI PT. PERMANA SIDAT INDONESIA - Monicha Ayu Maulani; Sukaris (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
Currently, developments in the increasingly advanced business world have led to increasingly fierce competition. One way to maintain the survival of the company is to maintain good relationships with customers. Because from research results retaining existing customers is much easier than getting new customers. Very tight business competition will really require strategic steps to deal with it. Old customers must be maintained by paying attention to all customer needs and also satisfying customer service. For new customers, efforts are made to become regular customers, by building relationships with customers. Companies engaged in the sale of goods such as companies engaged in the sale of motorcycles are facing stiff competition. It is very important to know and meet customer needs quickly and precisely. The presence of Customer Relationship Management (CRM) will be able to overcome the above problems because the purpose of CRM is to get the core of the unclear customer concept and put it in the application framework. One of the steps that can also be taken to deal with this problem is to utilize the technology and existing marketing concepts, namely the use of IT-based CRM (Customer Relationship Management). To be able to take advantage of this CRM needs to be built first in stages. The current condition of trading companies in the field of motorcycle sales will be explored and observations will be made on the need for services that can be provided to customers. In the process, CRM shows how marketing works and the system that is run must be able to support the company's environment with customers. Keywords : Customer, Customer Relationship Management, Customer Satisfaction, Customer Needs,